Production of 2,3-butanediol from blackstrap molasses - Sen Gupta, I.; Ibrahim, S.; Ramachandran, K.B. (2001)
2,3-Butanediol is an important chemical feedstock. Blackstrap molasses, which is the residual liquor after crystallization of brown sugar from sugar cane syrup was used as the substrate to produce 2,3-butanediol. Klebsiella oxytoca was used as the microorganism. Batch fermentation runs were carried out under moderately aerobic conditions in a 5 L fermenter at 37Â°C and pH 6.4. The combined yield of butanediol and acetoin was > 22 wt of the total sugar. Product yield could be doubled to 44 wt in batch fed operation. A value-added substance like 2,3-butanediol can be produced from an agricultural waste like blackstrap molasses by fermentation.